2019
DOI: 10.1186/s40659-019-0246-3
|View full text |Cite
|
Sign up to set email alerts
|

Stress and defense responses in plant secondary metabolites production

Abstract: In the growth condition(s) of plants, numerous secondary metabolites (SMs) are produced by them to serve variety of cellular functions essential for physiological processes, and recent increasing evidences have implicated stress and defense response signaling in their production. The type and concentration(s) of secondary molecule(s) produced by a plant are determined by the species, genotype, physiology, developmental stage and environmental factors during growth. This suggests the physiological adaptive resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
589
0
27

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 970 publications
(634 citation statements)
references
References 343 publications
(471 reference statements)
18
589
0
27
Order By: Relevance
“…As shown in several studies, the application of MeJA increased the resistance of the Norway spruce (Picea abies) to the root pathogen Pythium ultimum Trow [166], induced the expression of the 14-3-3 gene in the spruce plant [Picea glauca (Muench) Voss] [167], and accumulated a high amount of paclitaxel in several Taxus species [168]. The accumulation of JA in response to wounding is a common physiological feedback among all vascular plant species [1]. Therefore, JA has evolved as a plant hormone for stress adaptation, beginning with the emergence of vascular plants.…”
Section: Roles Of Jasmonic Acid In Plant Species Other Than Angiospermsmentioning
confidence: 96%
See 1 more Smart Citation
“…As shown in several studies, the application of MeJA increased the resistance of the Norway spruce (Picea abies) to the root pathogen Pythium ultimum Trow [166], induced the expression of the 14-3-3 gene in the spruce plant [Picea glauca (Muench) Voss] [167], and accumulated a high amount of paclitaxel in several Taxus species [168]. The accumulation of JA in response to wounding is a common physiological feedback among all vascular plant species [1]. Therefore, JA has evolved as a plant hormone for stress adaptation, beginning with the emergence of vascular plants.…”
Section: Roles Of Jasmonic Acid In Plant Species Other Than Angiospermsmentioning
confidence: 96%
“…Plants grow in environments that impose a variety of biotic and abiotic stresses. The primary abiotic stresses that influence plant growth include light, temperature, salt, carbon dioxide, water, ozone, and soil nutrient content and availability [1], where the fluctuation of any of these can hamper the normal physiological processes. Being static organisms, plants are unable to avoid abiotic stresses simply by moving to a suitable environment.…”
Section: Introductionmentioning
confidence: 99%
“…The electrical conductivity of the water in the soil was measured and showed a relatively high NaCl content at Agronomy 2020, 10, 410 9 of 12 about 0.95% to 1.12% ( Figure S3), which indicated that SR86 has a high salt tolerance compared with other rice varieties. The different performance of SR86 between soil and hydroponic conditions might be attributed to the complex soil environment, such as the soil microorganisms, root exudates, and interaction between the plants and soil microenvironment [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…They are known to be able to tolerate extreme weather conditions. It is known that the plant extracts synthesized by plants are affected by environmental factors, such as the temperature and the availability of water [17,18]. Therefore, the extracts from plants obtained from the Middle Eastern region may provide an array of different compounds with greater variety of bioactivities due to the environmental conditions surrounding these plants.…”
Section: Introductionmentioning
confidence: 99%